Dynamics of a Transportation Network Model with Homogeneous and Heterogeneous Users - Yingguo Li; Zhijia Tan; Qiong Chen (Discrete Dynamics in Nature and Society)
This paper studies the dynamics of the traveler's day-to-day route adjustment process in the general transportation network with fixed or elastic demand and homogeneous or heterogeneous users. Each traveler is assumed to adjust his/her route choice according to the excess travel cost between the instantaneous experienced travel cost and a certain referred level, which induces an aggregate path flow dynamics. We call the path flow dynamics the excess travel cost dynamics, which corresponds to the excess payoff dynamics in evolutionary games and serves a general framework of modeling the homogeneous or heterogeneous route choice behavior of travelers.